Evaluating Errors in Exam Papers for Benin Language Programs Credibility - Hounnou, Azoua Mathias (Innovare Journal of Education, 2024)
Evaluating errors represents an important shortcoming of the teaching-learning evaluation process in every educational system. The purpose of this research was to investigate the causes, consequences, and approaches of solutions to eradicate the evaluating errors in Benin secondary schools. To that purpose, ten (10) teachers and 100 learners were chosen based on their willingness exclusively from GUEMA secondary school in the municipality of Parakou. The data were collected through questionnaires, interviews, group discussions, and past exam papers analysis. The findings revealed that exam paper errors are often due to the evaluating system that consists of machines. The mistakes concern miswritten words, special notes such as “NB,” “Note,” etc., ambiguity about items and questions, and unreadability of the paper. Consequently, evaluating errors impacts the learners’ present and future language careers. They make learners feel demotivated and stressed, damaging their eagerness to learn the language. To solve this issue, it was shown that English as a Foreign Language (EFL) teachers need in-service training and significant reforms in evaluating the system should be done.